Application of Universal Design Principles in Public Spaces for Persons With Disabilities - Zulpiani, Mardhatillah; Rusyani, Endang (Journal of ICSAR, 2023)
People with disabilities also need ease of accessibility anywhere that allows them to do all the activities without any interruption of access in order to realize the similarity of opportunity in all aspects of life and livelihood that will aim to realize the independence of those who have obstacles, both physical, intellectual and other. Ease of access to public space is one of the rights to which are owned by them, therefore we need to pay attention to universal design principles so that they also get the right and the opportunity to enjoy the facilities provided by the government. In this research, using library research (library research). The study of literature is a study by using the method of data collection library, or in other words a research object of research is sourced from a variety of literature such as books, encyclopedias, journals and scientific articles. As a result, the application of universal design principles in public spaces for persons with disabilities is still lacking and needs attention. Public space should be a comfortable place for people with disabilities to do activities like the general public.